Application of the Principle of Legal Certainty in Land Ownership Disputes in Pantai Sari Ringgung - Izqo Seprian Maki; Rohaini Rohaini; Dianne Eka Rusmawati; Yulia Kusuma Wardani; Siti Nurhasanah (SEAN Institute, 2026)
This article analyzes the judicial reasoning and legal consequences arising from a land ownership dispute in Pantai Sari Ringgung, Pesawaran Regency, with particular attention to the application of legal certainty in Supreme Court Decision Number 3153 K/Pdt/2021. This article was adapted from an undergraduate thesis and reorganized into journal format without changing its core substance. This article uses normative legal research with a descriptive character and a judicial case study approach. The primary legal materials consist of the 1945 Constitution, the Basic Agrarian Law, the Criminal Code, Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency Number 21 of 2020, and decisions of the district court, the appellate court, and the Supreme Court examined in this dispute. Secondary materials include books and journal articles on land registration, land certificates, overlapping claims, and dispute resolution. The findings indicate that the appellate and cassation courts prioritize administratively valid documentary evidence over factual control and historical claims unsupported by legal ownership rights. Legal certainty is achieved through the recognition of valid land registration data, the validity of evidence from deleted certificates and photocopied documents, and the rejection of claims filed without legal basis. This decision directly impacts the parties by eliminating the plaintiff's legal basis and strengthening the defendant's protected legal position.